Cameroon : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Cameroon's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). Cameroon has been hit by significant export price declines and security threats since 2014. Oil revenue declined and security and humanitarian spending increased, while large infrastructure programs continued, leading to widening fiscal and current account deficits, rapidly accumulating external debt and a decline in imputed reserves. The Cameroonian authorities are requesting a three-year program under the ECF in the amount of SDR 483 million to restore external and fiscal sustainability, and lay the foundations for sustainable, private-sector led growth. The IMF staff supports the authorities' request for an ECF-supported program.